The Impact of Industrial Growth on the Manufacturing Trade Balance: An Aggregate and Industry-Level Analysis - Febrini Khairunnisa; Hermanto Siregar; Widyastutik (Buletin Ilmiah Litbang Perdagangan, 2025)
This study analyzes the impact of industrial growth—measured using the Industrial Production Index (IPI)—on Indonesia’s manufacturing trade balance during the 2014–2024 period, using both aggregate and sectoral approaches. An Autoregressive Distributed Lag (ARDL) model was used, incorporating the wholesale price index, the real effective exchange rate, and world oil prices as control variables, as well as two structural breaks: the COVID-19 pandemic and the foreign exchange policy on export proceeds. The results indicate significant heterogeneity across industries. At the aggregate level, an increase in the IPI tends to worsen the trade balance due to dependence on imported inputs, while in the food industry, an improvement occurs alongside industrial expansion. The wholesale price index supports an improvement in the aggregate trade balance but has a negative impact on the food sector, whereas the real effective exchange rate only improves the trade balance in the long run, confirming the Marshall–Lerner condition. The COVID-19 pandemic was associated with a temporary improvement in the trade balance due to a decline in imports.